Shift work and risk of incident gastroesophageal reflux disease: the association and mediation - Li, Qian; Li, Fu-Rong; Zhen, Shihan; Liao, Jian; Wu, Keye; Li, Xia; Wei, Bincai; Xiao, Zhiyi; Wu, Qingyao; Wu, Xian-Bo; Liang, Fengchao (Frontiers in Public Health, 2023)
Shift work has become an increasingly common work mode globally. This study aimed to investigate the association between shift work and the risk of incident gastroesophageal reflux disease (GORD), an upward gastrointestinal disorder disease worldwide, and to explore the mediating factors. A total of 262,722 participants from the UK Biobank free of GORD and related gastrointestinal diseases were included to investigate the association and potential mediators between shift work and incident GORD. Multivariate-adjusted Cox models were used to evaluate the association between shift work status and GORD incidence. Compared to non-shift workers, shift workers had a 1.10-fold greater risk of incident GORD (95% confidence intervals [CIs]: 1.03, 1.18), after adjusting for a range of potential confounders. However, the excess risk of GORD attenuated to the null after further adjusting for selected mediators. Specifically, the association was mediated by sleep patterns (25.7%), healthy behaviours (16.8%), depressive symptoms (20.2%), chronic conditions (13.3%), and biological factors (17.6%). After adjustment for all the mediators together, the association was attenuated by 71.5%. Our findings indicated that long-term shift workers may have a higher risk of incident GORD, yet the excess risk may be explained by poor sleep quality, unhealthy behaviours, depressive symptoms, etc. This has positive implications for protecting the health of shift workers.